Exposure to a Virtual Environment Induces Biological and Microbiota Changes in Onset-of-Lay Hens - Redweik, Graham A. J.; Millman, Suzanne T.; Parsons, Rebecca L.; Hurtado Terminel, Alejandro N.; Radkowski, Rafael; Daniels, Karrie; Lyte, Mark; Oliver, James; Mellata, Melha (Frontiers in Virtual Reality, 2022)
Increasing demand for cage-free eggs arises from goals to provide hens with better welfare, particularly in terms of natural behavior. However, most laying hens are kept in conventional cages, and cage-free systems, which can present challenges such as injuries, floor eggs, and bacterial infections. We propose using virtual reality (VR) as a feasible means for combining the positive attributes of natural environments while mitigating health risks. To our knowledge, no animal study has provided evidence that VR can trigger biological changes to improve animal health and well-being nor whether VR can affect the gut microbiome. In this study, we used VR technology to simulate a natural environment in laying hen housing. Early-lay White Leghorn hens were placed in pens with (VR) or without (CON) video projections displaying free-range chickens interacting with indoor and outdoor environmental features over five days. Using in vitro blood bactericidal assays, VR hens exhibited higher resistance against avian pathogenic Escherichia coli versus CON (P < 0.05), which was positively associated with corticosterone levels (P < 0.01). Analyzing intestinal neurochemicals via UHPLC, salsolinol was the only neurochemical metabolite affected by VR, being greater in CON ileal content (P < 0.0001), in VR ileal mucus (P < 0.01), and in VR ceca tissue (P < 0.05). Using 16S rRNA sequencing and QIIME2 analyses, no differences in alpha nor beta diversity were determined between groups. Although several genera (Megamonas, Ruminococcus, Slackia) were reduced in VR hens versus CON, Mucispirillum schaedleri (member of Deferribacteres Phylum) was the only taxon increased in VR hens, being elevated in ileal mucus (P < 0.05). Lastly, using the QIIME2 plugin mmvec to map microbe-metabolite co-occurrences, we identified several positive relationships between bacterial phyla and neurochemical metabolites, notably finding dopamine and salsolinol levels were related to Deferribacteres and Tenericutes levels. In conclusion, we found that several biological parameters were influenced by VR treatment in hens, suggesting that VR can be used to modulate bacterial resistance and gut health in poultry.